Medical Image Computing and Computer Assisted Intervention – MICCAI 2020 : 23rd International Conference, Lima, Peru, October 4–8, 2020, Proceedings, Part II /: 23rd International Conference, Lima, Peru, October 4–8, 2020, Proceedings, Part II. (2020) - Unknown
No abstract available